PENGEMBANGAN MODUL PROJEK PENGUATAN PROFIL PELAJAR PANCASILA DENGAN TEMA KEARIFAN LOKAL UNTUK KELAS IV DI SDN 2 MRANTI - Karomatul Sa’bani; Nur Ngazizah; Suyoto (Jurnal Binagogik, 2024)
This development research aims to (1) produce a project module to strengthen the profile of Pancasila students with the theme of local wisdom for class IV elementary schools. (2) Knowing the feasibility of the project module to strengthen the profile of Pancasila students with the theme of local wisdom for class IV elementary schools. The research design uses Research and Development (R&D) with the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). The designs used are limited trials and wider trials. Data collection techniques include observation, interviews, questionnaires and tests. The instruments used were validation sheets, student response questionnaire sheets, learning implementation sheets, and effectiveness. The research subjects were class IV students at Mranti Elementary School. This research resulted in: (1) producing a project module to strengthen the profile of Pancasila students with the theme of local wisdom. (2) The appropriate basis for use is based on aspects of validity, practicality and effectiveness. In the validity aspect, validation was carried out by material experts getting a percentage of 95% and media experts getting a percentage of 90% in the very valid category. The practical aspect of student responses during limited trials had an average percentage of 93%, while extensive trials had an average percentage of 95%. Judging from the results of student responses and the results of the learning implementation of the project module for strengthening the profile of Pancasila students, the criteria were very practical. The effectiveness of the project module for strengthening the profile of Pancasila students can be seen from the n-gain score of 0.76 in the effective category so that the project module for strengthening the profile of Pancasila students is declared effective for use in learning.